Analisis Tindak Tutur Ekspresif Dan Direktif Dalam Video Debat Pembelajaran Bahasa Indonesia Kelas X Pada Channel Youtube Guru Gokil Kita - Dinda Puspita Rini; Muhammad Farchan Muntaha; Sunaryo Sunaryo; Kholifatun Nisya; Mutia Basinu; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Speech acts are the activities of speakers using language with their interlocutors to convey something. The research we conducted was analyzing speech acts contained in Indonesian language learning debate videos on the Guru Gokil Kita YouTube channel. This article is intended to be aware of the number of speech acts, namely expressive speech acts and directive speech acts in Indonesian language learning debate videos on the Guru Gokil Kita YouTube channel. Qualitative descriptive is the research technique that we use. The data used and found in this research are in the form of speech sourced from the debate video and analyzed in line with the type of speech act that the author will analyze. The video listed was taken from the Guru Gokil Kita YouTube channel which was broadcast in 2019. The researcher used the note-taking method as a method of collecting research results. Qualitative techniques are techniques used to analyze data in the form of speech in this research activity. The analysis results obtained after analyzing the three videos found that there were 55 expressive speech acts and 102 directive speech acts. Expressive speech acts consist of praising, thanking, flattering, blaming, complaining and criticizing. Meanwhile, directive speech acts consist of ordering, giving orders, suggesting, inviting, urging, convincing, and begging. The results of this research have the potential to contribute to the field of linguistics, especially in the context of pragmatics related to everyday use of spoken language. In addition, this research can function as a useful reference source to support further research in the field of linguistics.